Pembangunan Aplikasi Informasi Kesehatan Masyarakat Kota Malang Berbasis Mobile Native Android - Ferdy Wahyurianto; Issa Arwani; Arief Andy Soebroto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The population of the society will continue to evolve over time, this makes process of logging society's health data will be more difficult to do. The problem is becoming a foundation in developing technology to ease the process of logging society's health quickly. The society's health information used by the Government in serving and improving the welfare of the society. The society's health information technology at Malang present day is based with website which requires a static place and low mobility. The solution to this problem is by developing a mobile app that is more practical and much sought present day, because it gives convenience to access information and high mobility support. Solutions offered the author is building a society's health information system based on mobile native app using the android platform because the majority of 89.75% of society use android operating system. System development method using the waterfall method that supports development in accordance with the needs of users who are clearly defined at the beginning. This Application can process and projecting the amount of society's health data distribution into Google Maps. The system is tested by doing unit testing, validation testing, as well as the compatibility testing. The results of the testing analysis on this system meets the needs of users as well as being able to support the system's performance and high mobility.